Healthcare data management, regarding the growing popularity of precision medicine - Maciejewska Katarzyna (2019)
Precision medicine that is studying DNA-based diseases is gaining more and more popularity in the world thanks to the dynamic development of sequencing technology. In 2003, the Human Genome Project (HGP, Human Genome Project) was completed, lasting 15 years and costing 2.7 billion dollars. Currently, the cost of running a genome test is around USD 1,000 and lasts only a few hours to several days, depending on the technology chosen. This document contains the most important concepts related to precision medicine and healthcare data management. Due to the significant reduction in costs associated with carrying out genetic tests, they have become more available and can be taken into account in patient studies. The techniques and methods discussed generate a large amount of medical data that should be managed and also used in preventive healthcare.